Effect of Solvent on Surface Ordering of Poly(3-hexylthiophene) Thin Films - Xiao, Minyu (Langmuir : the ACS journal of surfaces and colloids, 2015)
Enhancement of charge transport in organic polymer semiconductors is a crucial step in developing optimized devices. A variety of sample preparation conditions, such as film fabrication method, solvent species, and annealing, were found to influence the hole mobility of organic polymers. Despite the fact that many factors can influence their performance, it is believed that polymer surface ordering plays a key role in determining organic polymer function. Here, sum frequency generation (SFG) vibrational spectroscopy was used to nondestructively map the surface/interfacial ordering of poly(3-hexylthiophene) (P3HT) films prepared using different solvents; we believe that solvent interactions determine the degree of surface/interfacial ordering. Both X-ray diffraction (XRD) spectroscopy and scanning electron microscopy (SEM) were used to supplement SFG to systematically study bulk crystallinity and surface morphology. We conclude that SFG is a powerful tool to elucidate the surface/interfacial structural information on polymer semiconducting films. We demonstrate that the solvent composition used to prepare P3HT thin films influences the resulting film surface morphology, surface/interfacial ordering, and bulk crystallinity